Doctoral identity change towards researcher autonomy during research journeys across disciplines - Bitzer, Eli; Van den Bergh, Stephanie (South African Journal of Higher Education, 2016)
With some understanding of doctoral identity comes a focus on the ways in which candidates both shape and are shaped by research milieus and contexts. Doctoral identity is thus both a continuous conscious and unconscious process influenced by interacting elements such as biological characteristics, own unique psychological needs, interests and defences as well as and the cultural milieu or context in which doctoral candidates operate. This brings forth the idea of doctoral identity formation as a doctoral ‘journey’ towards researcher autonomy. Employing a researcher development framework, this article elaborates on research conducted on how doctoral education seems to have mattered for seven doctoral graduates across five disciplinary areas in terms of identity change as demonstrated in becoming more autonomous as researchers. Findings indicate identity changes in six dimensions, namely curiosity, determination, criticality, organisation, creativity and persuasion. The research finding indicate that doctoral graduates seem to differ in moving towards researcher autonomy within their distinctive doctoral journeys and therefore may also differ in the nature and tempo of identity formation as independent or autonomous researchers. A conceptual framework is suggested which may assist doctoral supervisors in gaining a better understanding of the processes and dynamics involved in doctoral identity formation towards researcher autonomy at research-led universities.